تناوب حروف الجر في ديوان امرئ القيس دراسة وصفية تحليلية - الذنيبات, أحمد عبد الرحمن; محمود الفراية, نضال (Revues faculté des lettres et des langues; No 9 (2011): مجلة كلية الآداب واللغات, 2014)
يرمي هذا البحثُ إلى الكشفِ عن تناوبِ حروفِ الجرّ في ديوان امرئ القيس، وأنّ مسألة التناوب بين حروف الجرّ مسألةٌ أباحتها اللّغة لأبنائها قدماء ومحدثين على غير ما ذهب إليه بعضُ علماء العربيّة؛ كقول بعض القدماء البصريين بالتضمين بدلاً من التناوب، وتبعهم بعض المعاصرين في القول بأنّ تناوبَ بعض الحروف سماعيّ لا يجوز القياس عليه، لذا نهض هذا البحث على تعريف مفهومي التناوب و التضمين، وتوضيح أنَّ التضمين فيه بعد عن المعنى المراد من الفعل، ثم بسطَ البحثُ الأمثلةَ والشواهدَ من الديوان متتبعاً مواضع التناوب في مظان كتب اللغة وخصوصاً تلك التي اهتمت بالحروف ومعانيها.وخلص البحث إلى أن هذه المسألة لم تخرج عن طريق العرب في التعبير، وأنّه بالإمكان القياس عليها في لغة المحدثين.   This research aims at investigating the alternation of the prepositions in the poetry of  Emre ol-Qais. The alternation of the prepositions is a matter which is allowed by Arabic language to be used by its people, the ancient and the modern. This is not as  stated by some of the Arabic scholars. For instance, some of the ancient Basrees who used connotation instead of alternation. These were followed by the contemporary who said that the alternation of some prepositions are auditory by which can not be measured. Thus, this research is an attempt to define both  concepts, alternation and connotation. It also shows that connotation is far from meaning which is required from the verb. Then, the researcher explains examples and evidence tracing the locations of alternation in language books, particularly, those which are concerned with prepositions and their meanings. The researcher concludes that this topic has not gone far from the Arab  route of expression, and that it is possible to measure on it in the modern language.